2018
DOI: 10.5530/ijopp.11.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Tool Based Detection of Adverse Drug Reactions in a Tertiary Care Teaching Hospital: A Prospective Observational Study

Abstract: Background: The use of "triggers" to identify Adverse Drug reactions (ADRs) is a novel emerging method for measuring the overall level of harm from medications in a health care organization. Our main objective is to determine the incidence of adverse drug reactions in the hospitalized patients and to compare Global Trigger Tool (GTT) with conventional method to identify ADRs. Methodology: A Prospective observational study was conducted over a period of six months during November 2016-April 2017. Modified Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has been reported that deaths due to ADRs contributed to 1.8% of the total deaths in India. 6 Therefore, setting up ADR monitoring centers at a more regional or hospital level and integrating them with a sound network can reveal unusual or rare ADRs prevalent in the Indian population.…”
Section: Epidemiologymentioning
confidence: 99%
“…It has been reported that deaths due to ADRs contributed to 1.8% of the total deaths in India. 6 Therefore, setting up ADR monitoring centers at a more regional or hospital level and integrating them with a sound network can reveal unusual or rare ADRs prevalent in the Indian population.…”
Section: Epidemiologymentioning
confidence: 99%